2021
DOI: 10.21776/ub.civense.2021.00401.1
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Impact on Potentially Liquefactions Slope Deformation

Abstract: In an area that has potential for earthquake has possibility of losing soil stability and causing physical soil damage, one of them is liquefaction. This research was conducted to determine the magnitude of deformation on slopes with potentially liquefaction. The soil slope samples were tested using shaking table with slope 6°, 12°, 18°, 24° and the frequency was set 6.6 Hz, 7.4 Hz, 8 Hz, 9.5 Hz. Research began with examination of soil physical properties which had unit weight of density 1.81 gr/cm3, moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…It added mark speed in something range time called acceleration. This study used acceleration earthquake, however conversion acceleration to frequency for input to in tool, with formula as follows according to [23]. 5 can monitor the movement of the ground, which in this case, measures the subsidence in the ground during the shaking test.…”
Section: Sand Rainer Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…It added mark speed in something range time called acceleration. This study used acceleration earthquake, however conversion acceleration to frequency for input to in tool, with formula as follows according to [23]. 5 can monitor the movement of the ground, which in this case, measures the subsidence in the ground during the shaking test.…”
Section: Sand Rainer Boxmentioning
confidence: 99%
“…This is the same as the research conducted by [2], this study found that as the relative density of the soil increases, the decrease will be smaller. Research by [23] concluded that the greater the frequency given, the greater the deformation that occurs. Comparison of the decrease that occurs with the increase in relative density values of 40% and 70% at a frequency of 1 Hz is 10%, and at a frequency of 1.2 Hz is 29%.…”
Section: Pore Water Pressure Measurementmentioning
confidence: 99%